Ranolazine Improves Glycemic Variability and Endothelial Function in Patients with Diabetes and Chronic Coronary Syndromes: Results from an Experimental Study - Annunziata Nusca; Federico Bernardini; Fabio Mangiacapra; Ernesto Maddaloni; Rosetta Melfi; Elisabetta Ricottini; Francesco Piccirillo; Silvia Manfrini; Gian Paolo Ussia; Francesco Grigioni (Journal of Diabetes Research)
Background. Ranolazine is a second-line drug for the management of chronic coronary syndromes (CCS). Glucose-lowering and endothelial effects have also been reported with this agent. However, whether ranolazine may improve short-term glycemic variability (GV), strictly related to the prognosis of patients with type 2 diabetes (T2D), is unknown. Thus, we aimed to explore the effects of adding ranolazine to standard anti-ischemic and glucose-lowering therapy on long- and short-term GV as well as on endothelial function and oxidative stress in patients with T2D and CCS. Methods. Patients starting ranolazine (n=16) were evaluated for short-term GV, haemoglobin 1Ac (Hb1Ac) levels, endothelial-dependent flow-mediated vasodilation (FMD), and oxidative stress levels at enrolment and after 3-month follow-up. The same measurements were collected from 16 patients with CCS and T2D that did not receive ranolazine, matched for age, gender, and body mass index. Results. A significant decline in Hb1Ac levels was reported after 3-month ranolazine treatment (mean change -0.60%; 2-way ANOVA p=0.025). Moreover, among patients receiving ranolazine, short-term GV indexes were significantly improved over time compared with baseline (p=0.001 for time in range; 2-way ANOVA p=0.010). Conversely, no significant changes were reported in patients without ranolazine. Finally, greater FMD and lower oxidative stress levels were observed in patients on ranolazine at 3 months. Conclusions. Ranolazine added to standard anti-ischemic and glucose-lowering therapy demonstrated benefit in improving the glycemic status of patients with T2D and CCS. How this improvement contributes to the overall myocardial benefit of ranolazine requires further studies.